1999
DOI: 10.1007/bf02345573
|View full text |Cite
|
Sign up to set email alerts
|

Application of radioisotopes in the field of nuclear medicine

Abstract: A comprehensive review has been made to discuss the role of various radionuclides of lanthanide series elements in the field of nuclear medicine. The role of several pharmaceuticals labeled with radiolanthanides and used for investigative purposes like measurement of cerebral blood flow, bone density measurement, bone marrow imaging, etc., have been described. The role of lanthanide radionuclides in radiation synovectomy, radioimmunotherapy, etc., have also been discussed. Methods of preparation of some repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 65 publications
1
29
0
1
Order By: Relevance
“…Activation cross section on Tb are required for production of the medically relevant 159 Dy (Nayak et al, 1999) and 157 Dy (Lebowitz et al, 1971, Yanao et al 1972, Apo, 1981 Our results on deuteron induced reactions on terbium were published by Tarkanyi et al, 2013. We decided to continue the investigations to compare the production possibilities of the proton and deuteron induced routes.…”
Section: Introductionsupporting
confidence: 57%
“…Activation cross section on Tb are required for production of the medically relevant 159 Dy (Nayak et al, 1999) and 157 Dy (Lebowitz et al, 1971, Yanao et al 1972, Apo, 1981 Our results on deuteron induced reactions on terbium were published by Tarkanyi et al, 2013. We decided to continue the investigations to compare the production possibilities of the proton and deuteron induced routes.…”
Section: Introductionsupporting
confidence: 57%
“…[63,67,[107][108][109][110] To mention some examples, various lanthanide complexes and nanoparticles are used as luminescent labels in various fluoroimmunoassays, [110] the application of Gd 3+ complexes as contrast agents for magnetic resonance imaging (MRI), [111][112][113] and the employment of radioactive rare-earth isotopes as radiopharmaceuticals. [114] The usage of biologically relevant ligands such as amino acids leads to the formation not only of mononuclear complexes, but also of oligo-and polynuclear rare-earth metal clusters. [3,63] Zheng et al reported not only on a pentadecanuclear cluster with tyrosine as a supporting ligand as stated above, [41,68] but also on a chiral 60-metal sodalite-like structure based on erbium and use of L-threonine (L-Thre) as a ligand (Figure 8).…”
Section: Properties and Applications Of The Pentanuclear Clustersmentioning
confidence: 99%
“…The lanthanides 153 Gd (T 1/2 = 240.4 days) finds application in single photon emission computed tomography (SPECT) used for diagnosing neurological disorders, cardiac blockages or abnormalities, and primary and metastasized cancer. 153 Gd is also used in industrial radiography, for ascertaining the strength and integrity of structural materials and piping systems [29][30][31]. Recently terbium radionuclides, especially 149 Tb (T 1/2 = 4.11 h) is under focus as an excellent radionuclide for targeted therapy.…”
Section: Applicationsmentioning
confidence: 99%